Si Lupito at ang barrio sirkero Lupito and the circus village - Almazar, Rowald; Santos, Jose; Wigley, John Jack; Capili, Jose Wendell P.; Tayona, Daniel Palma; Cheung, Mike (Manila UST Publishing House, 2008)
Canvas proudly presents a new and whimsical tale of courtship and courage in a circus village.
Text in English and Filipino.
"Originally written in Filipino."
"All artworks originally rendered in oil on canvas."
"Canvas stories. Real life told beautifully."
Keywords: Short stories, Philippine (English); Filipino short stories